Identifikasi Potensi Pangan Lokal untuk Penganekaragaman Produk Pangan Kota Balikpapan - Gozali Gozali; Bambang Jati Kusuma (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
The purpose of this study was to determine the potential of superior local food in the Balikpapan City. The method used in this research is descriptive method. Data collection techniques using the location survey and institutional survey methods. The identification of local food potential in the Balikpapan City in this study in terms of the food sector in terms of availability. Based on the results of data analysis that has been carried out in the city of Balikpapan, there are about 12 (twelve) types that are widely cultivated by farmers, namely: sweet corn, papaya, banana, cempedak, lai / durian fruit, dragon fruit, sweet potato / wood, pineapple, salak, and rambutan. Although some other plants are also found, but relatively few in number, such as tomatoes, cucumber, guava, and others. The existence of local food in the Balikpapan City area has the potential to be developed into various food products